Democratic citizenship and polarization: Robert Talisse’s theory of democracy - Sharp, Daniel B. (Ethical theory and moral practice, 2022)
This review essay critically discusses Robert Talisse’s account of democracy and polarization. I argue that Talisse overstates the degree to which polarization arises from the good-faith practice of democratic citizenship and downplays the extent to which polarization is caused by elites and exacerbated by social structures; this leads Talisse to overlook structural approaches to managing polarization and leaves his account of how citizens should respond to polarization incomplete. I conclude that Talisse’s insights should nevertheless be integrated into a broader agenda for thinking about the causes and solutions to polarization.